Preface - Petridou, Lydia (Dia-noesis: A Journal of Philosophy, 2024)
This is a special volume dedicated to Philosophy in Late Antiquity and, more specifically, to Middle Platonism, Neopythagoreanism, and Neoplatonism. It includes articles that focus on philosophical concepts and theories that emerge during this particular period of time, which can relate to any philosophical branch.